Suburban Community Settlement in Makassar City (Qualitative Study of Health Education in Efforts to Improve Community Healthy Lifestyle) - Jusmawandi Jusmawandi (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2022)
Fisherman's Village, precisely in Untia Village, Biringkanaya District, Makassar City, is one of the villages located on the west side of Makassar City. This village is often a subscriber of news related to unhealthy housing conditions. The role of the Makassar City Government is realized with the slogan